Economic Inequality in Australia: a reassessment - Fenna, Alan; Tapper, Alan (Taylor and Francis, 2015)
This article reviews and analyses the evidence on the distribution of income and wealth in Australia since the 1960s. A number of scholars – most prominently among them Thomas Piketty – suggest that inequality has been increasing across the advanced capitalist world. Kuznets’ benign picture of an ‘inverted u-curve’ depicting declining inequality in modern industrial society is replaced with an altogether different and potentially quite alarming one. Does this hold for Australia? Surveying 25 income trend and 17 wealth distribution studies, we draw on the best available evidence and find that overall there has been far less of a rising inequality trend than is often assumed or argued.